(untitled) (Palíndromo, 2024)
Appreciating an artwork is a complex activity that requires the development of skills: skills to exploit one’s imagination; skills to exploit one’s sensitivity; skills to examine a work of art. It also requires skills to synthesize what has been felt, imagined and examined. The article presents the “SIR” approach, a proposal for appreciating works of art according to three stages, in this order: 1) feeling and imagining; 2) examine the content elements and sociocultural elements of the artwork; 3) summarize the first two steps to establish a critical and aesthetic judgment. It is an appreciation process that can be carried out by art teachers and other educators and aims to develop sensitive, imaginative, analytical and synthetic skills.